Bone‐Targeted Fluoropeptide Nanoparticle Inhibits NF‐κB Signaling to Treat Osteosarcoma and Tumor‐Induced Bone Destruction - Lin Li; Guangyu Rong; Xin Gao; Yiyun Cheng; Zhengwang Sun; Xiaopan Cai; Jianru Xiao (Advanced Science)
Abstract Osteosarcoma is a malignant bone cancer usually characterized by symptoms of bone loss due to pathologically enhanced osteoclast activity. Activated osteoclasts enhance bone resorption and promote osteosarcoma cell progression by secreting various cytokines. Intercepting the detrimental interplay between osteoclasts and osteosarcoma cells is considered as an option for osteosarcoma treatment. Here, a bone‐targeted fluoropeptide nanoparticle that can inhibit the nuclear factor kappa B (NF‐κB) signaling in both osteoclasts and osteosarcoma to address the above issue is developed. The NF‐κB essential modulator binding domain (NBD) peptide is conjugated with a fluorous tag to improve its proteolytic stability and intracellular penetration. The NBD peptide is efficiently delivered into cells after fluorination to induce apoptosis of osteocarcoma cells, and inhibits osteoclasts differentiation. The fluorous‐tagged NBD peptide is further co‐assembled with an oligo (aspartic acid) terminated fluoropeptide to form bone‐targeted peptide nanoparticles for osteosarcoma treatment. The targeted nanoparticles efficiently inhibited tumor progression and osteosarcoma‐induced bone destruction in vivo. This co‐assembled fluoropeptide nanoplatform proposed in this study offers a promising approach for targeted and intracellular delivery of peptide therapeutics in the treatment of various diseases.